ASUHAN KEBIDANAN IBU HAMIL PATOLOGIS, BERSALIN FISIOLOGIS, NIFAS FISIOLOGIS, BAYI BARU LAHIR FISIOLOGIS, DAN KELUARGA BERENCANA FISIOLOGIS PADA NY F USIA 30 TAHUN DI PUSKESMAS WINONG KEMIRI KABUPATEN PURWOREJO - Zuliyanti, Nurma; Lijannah, Shofiana (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2024)
ABSTRACT Background: The level of public health is influenced by the existence of health service facilities. The success of maternal health programs can be assessed through the Maternal Mortality Rate (MMR). Efforts to improve the survival and quality of mothers and children are carried out using a continuum of care approach. Research objectives: To provide continuum of care midwifery care, it is necessary to carry out assessments, data interventions, diagnose problems, anticipate, manage, evaluate and discuss gaps between theory and practice of pregnancy, childbirth, postpartum, newborns and family planning and record developments carefully. SOAPIE. Results: The client had her pregnancy checked at 36 and 37 weeks of gestation, gave birth spontaneously at 39 weeks of gestation, the client's postpartum period had no complications. On the 30th day of the postpartum period, the client decided to use 3-month injectable birth control. Conclusion: the client experienced mild anemia during pregnancy and anticipation was carried out, while for labor, postpartum, newborn and family planning there were no complications and was in a physiological condition. Keywords: continuum of care, pregnant women, maternity, postpartum, newborn, family planning